Barriers of access and utilization of reproductive health services by adolescents-Khartoum state-Sudan-2020: study protocol - Mustafa Khidir Mustafa Elnimeiri; Shahenaz Seifaldeen Mustafa Satti; Mohanad Kamaleldin Mahmoud Ibrahim (BMC, 2020)
Abstract Background Adolescence is widely defined as the time in life when the developing individual attains the skills and attributes necessary to become a productive and reproductive adult. Most adolescents are healthy, but there is still substantial premature death, illness, and injury among adolescents. Illnesses can hinder their ability to grow and develop to their full potential. Alcohol or tobacco use, lack of physical activity, unprotected sex and/or exposure to violence can jeopardize not only their current health, but also their health as adults or even health of their future children. Method Community and institutional-based cross sectional study will be conducted in Khartoum State the seven localities will be included. This state is the national capital of Sudan, which has an area of 22,122 km2. The sample size of participant is estimated using the population formula (n = N/1+ (n*d2)). The sample will be drawn using multistage cluster sampling. Also the concerned bodies involved in the delivery of reproductive health services for adolescents included in this study. Data will be collected using interviews with key informants and administered pre-coded, pretested closed ended questionnaire with community participants. Data will be managed and analyzed using Statistical Package for Social Sciences version 21. Analysis is mostly univariate descriptive and bi-variate with Chi Square & Fischer Exact test analysis to find associations between variables of interest. Discussion The census of adolescents mounted to 25% of the population and thus it is important to care for such significant portion of the population to document their reproductive health problems and their access to health care services. The study is expected to generate base-line indicators about barriers of access to reproductive health services by adolescents that can be used for better planning, monitoring and evaluation of the delivered services. The research about barriers of access to reproductive health services by adolescents in Sudan is still limited and the information is scanty and scattered. Thus, it is necessary to conduct such study to enrich the current database.